(untitled) (Research, Society and Development, 2019)
Objective: identifying nursing care for cancer patients. Methodology: integrative review, the following descriptors were used: oncology nursing, oncology, nursing care to search for articles, the selected databases were: Scientific Electronic Library Online (SciELO), Virtual Health Library (VHL) , Regional Online Information System for Scientific Journals from Latin America, the Caribbean, Spain and Portugal (LANTIDEX). Results: after analyzing the data, we affirm that the main types of nursing care are: daily dressing, tracheal aspiration, vital signs verification, drainage care, bedside positioning and observation of bleeding, respiratory pattern, self-care in addition to caring for the patient’s family. Conclusion: based on these data, it can be observed that the main nursing care is related to direct care to the patient, but goes much further, involving the emotional care that involves these clients.